Desarrollo de un prototipo de criadero automático con ambiente controlado destinado a mejorar los índices de producción de huevos en la coturnicultura - Pushug Guacho, Juan Fernando (2017)
The present technical project, noting that coturniculture is an activity with good projection, of early capital recovery, but the process of technology in its processes, opens to develop a prototype of automatic kennel to correct the deficiencies that occur in the Traditional production The project is part of the information collected on the care and management of quail, in this way identifies what are the conditions in which they are during the laying period. Taking into account all the feet of quail care, the process has developed automatic crime, which has been imprisoned to maintain optimal conditions for: hydration, feeding, air conditioning, lighting and sanitation, with the Purpose of increasing egg production and decreasing mortality. For the program code, the parameters are set that the control system by reading the sensors and processing the data, performed control actions and in order to maintain the conditions established. This project also reduces the number of hours that the person in charge has to invest in the hatchery. In order to see the viability of the project for five months, the information on the production of traditional kennel eggs and the automatic kennel was collected, finding that the prototype of a requirement for improvement shows a significant increase in egg production, as well as Considerable in Mortality.